Assistência técnica e desempenho do professor - Melo, Maria Helena Pereira de (1977)
This work is the consequence of a research made in 1974, in Maranhão, at the towns of Imperatriz and Carolina, including alI the teachers of the four first series of the First Degree of the State's Official Network. Such a research aimed at verifying the performance of the Theacher Engaged in Technical -Educational Assistence Plan, as well as the Not Engaged.